Forgetting Follow - Collins, Christopher (Palgrave Macmillan, 2014)
This essay considers the award-winning performance of Follow by Irish theatre company, WillFredd Theatre. The essay considers Follow's performance of Irish Deaf collective memory and the importance of forgetting as a salutatory phenomenon for theatre historiography.